2000
DOI: 10.1007/s11926-000-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nervous system function in fibromyalgia

Abstract: This review focuses on studies of the sympathetic nervous system in fibromyalgia (FM). First, a brief review of the sympathetic system, and its relationship to the human stress response, is outlined. Then various studies of functional assessment of sympathetic function in FM are highlighted. Certain methods of assessment (eg, heart rate variability, biochemical, and psychophysical responses to various stressors) that we believe to be of specific importance for future research are discussed in greater detail. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 56 publications
3
51
0
1
Order By: Relevance
“…[4][5][6] Stress response plays an important role in the symptoms, and it is believed that the ANS has a close relationship with the efficiency of the stress response and the hypothalamic-pituitary-adrenal axis (HPA). [7] A simple and reliable neurophysiologic method to evaluate the ANS is the study of the sympathetic skin response (SSR). [8,9] Using an electrical stimulation, the eccrine sweat glands of the skin are activated via a reflex loop which includes large, myelinated sensory fibers, central synapses and efferent sympathetic preand post-ganglionic nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Stress response plays an important role in the symptoms, and it is believed that the ANS has a close relationship with the efficiency of the stress response and the hypothalamic-pituitary-adrenal axis (HPA). [7] A simple and reliable neurophysiologic method to evaluate the ANS is the study of the sympathetic skin response (SSR). [8,9] Using an electrical stimulation, the eccrine sweat glands of the skin are activated via a reflex loop which includes large, myelinated sensory fibers, central synapses and efferent sympathetic preand post-ganglionic nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies showed elevated function in the sympathetic nervous system. [4][5][6][7] Martinez-Lavin et al [19] suggested that fibromyalgia patients have norepinephrine-evoked pain which may be resolved by sympatholytic maneuvers. They also proposed that sympathetic hyperactivity may explain some of the manifestations of FMS including sleep disorders, irritable bowel syndrome, sicca symptoms and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate arousal of the sympathetic nervous system has also been demonstrated in fibromyalgia syndrome (28). But, autonomic tone depends on homeostatic balance.…”
Section: Discussionmentioning
confidence: 99%
“…The recognition that pain may be present in the absence of measurable clinical abnormality is now fully supported by objective neurophysiological study 19 . Abnormalities have been identified at various levels in the peripheral, central, and sympathetic nervous systems, as well as the hypothalamo-pituitary-adrenal axis stress-response system [20][21][22][23][24][25] .…”
Section: Acceptance Of the Concept Of Fmmentioning
confidence: 99%